2009
DOI: 10.1002/nur.20344
|View full text |Cite
|
Sign up to set email alerts
|

African American women's beliefs about mental illness, stigma, and preferred coping behaviors

Abstract: We examined African American women's representations/beliefs about mental illness, preferred coping behaviors if faced with mental illness, whether perceived stigma was associated with treatment-seeking, and if so, whether it was related to beliefs and coping preference, and whether these variables differed by age group. Participants were 185 community-dwelling African American women 25 to 85 years of age. Results indicated the women believed that mental illness is caused by several factors, including family-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 44 publications
5
44
1
Order By: Relevance
“…Moreover, in support of this finding, additional studies with this population have suggested that older, women in comparison to younger women may have greater resources for coping with a range of stressors (e.g., Ward and Heidrich 2009;Zauszniewski et al 2005). Recent work with African American adolescent girls also suggests that age may be an important background factor for understanding stress experiences (Slater et al 2001).…”
Section: Agementioning
confidence: 74%
“…Moreover, in support of this finding, additional studies with this population have suggested that older, women in comparison to younger women may have greater resources for coping with a range of stressors (e.g., Ward and Heidrich 2009;Zauszniewski et al 2005). Recent work with African American adolescent girls also suggests that age may be an important background factor for understanding stress experiences (Slater et al 2001).…”
Section: Agementioning
confidence: 74%
“…Subscale scores were created by taking a mean of the relevant items, with higher scores (closer to 4) indicating greater likelihood of coping in that way if faced with a mental illness. In previous research with African Americans, internal consistency alpha coefficients ranged 0.62-0.78 (Ward & Heidrich, 2009). In the present study subscale reliabilities ranged 0.64-0.84.…”
Section: Methodsmentioning
confidence: 94%
“…The PCS was developed specifically for African Americans and in previous unpublished research has demonstrated good construct validity. Ward & Heidrich (2009) found among African Americans acceptability construct validity and internal consistency alpha coefficients ranging from 0.62 - 0.708. In the present study subscale reliabilities ranged from 0.64 - 0.84.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations